Wpływ suszy na pobór wody przez sosnę zwyczajną (Pinus sylvestris L.) o różnej pozycji w drzewostanie - Boczoń, Andrzej; Wróbel, Michał (Leśne Prace Badawcze, 2015)
Periodically occurring drought is typical for the climate of Poland. In habitats supplied exclusively with rain water, tree stands are frequently exposed to the negative effects of water deficit in the soil. The aim of this study was to examine the water uptake and consumption of two individual Scots pine trees under drought conditions. The trees were located at different positions within the stand and at the time of study were over 150 years old. Soil moisture, availability of soil water and the quantity of water uptake by the individual trees were examined by measuring the water velocity inside the trunks (Thermal Dissipation Probe method). Two periods of intense drought occurred in the summer 2006 only a few days apart. Before the drought, pine No. 1 (dominant) took up 66.7 dm 3 water per day and pine No. 2 (co-dominant) took up 52.3 dm 3 per day. The observed responses of the examined pines to the first period of drought were similar: the low soil water content resulted in a suppression of water uptake in both trees. After the end of the drought period however, the recovery responses of the two trees were different. Pine No. 1 resumed water uptake at values similar to those before the drought. Pine No. 2 on the other hand did not resume water uptake. We conclude that in case of this second tree the vegetative season possibly ended already at the end of June.